2016
DOI: 10.21548/32-1-1371
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Volatile Composition of Mango Wines Fermented with Different Saccharomyces cerevisiae Yeast Strains

Abstract: The aim of this study was to compare the chemical and volatile composition of mango wines fermented with Saccharomyces cerevisiae var. bayanus EC1118, S. cerevisiae var. chevalieri CICC1028 and S. cerevisiae var. cerevisiae MERIT.ferm. Strains EC1118 and MERIT.ferm showed similar growth patterns but strain CICC1028 grew slightly slowly. The ethanol level reached about 8% (v/v) for each mango wine and sugars (glucose, fructose and sucrose) were almost exhausted at the end of fermentation. There were only neglig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…This was consistent with previous studies that showed that terpene hydrocarbons were the major volatiles of fresh mango juice, with cultivars such as Kaew, Obispo, Corazon, Huovo de Toro and Chok Anan containing high α-terpinolene contents (Macleod et al, 1988;Pino & Mesa, 2006;Li et al, 2011). Alcohols were the second dominant class of compounds, and (Z)-3-hexenol was the major one contributing a green and grassy odour (Pino et al, 2005;Li et al, 2011). However, ethanol was low in concentration in the fresh mango juice.…”
Section: Major Volatiles In Juicesupporting
confidence: 91%
See 4 more Smart Citations
“…This was consistent with previous studies that showed that terpene hydrocarbons were the major volatiles of fresh mango juice, with cultivars such as Kaew, Obispo, Corazon, Huovo de Toro and Chok Anan containing high α-terpinolene contents (Macleod et al, 1988;Pino & Mesa, 2006;Li et al, 2011). Alcohols were the second dominant class of compounds, and (Z)-3-hexenol was the major one contributing a green and grassy odour (Pino et al, 2005;Li et al, 2011). However, ethanol was low in concentration in the fresh mango juice.…”
Section: Major Volatiles In Juicesupporting
confidence: 91%
“…Terpenes are significant contributors to the unique mango aroma (Macleod et al, 1988;Pino et al, 2005;Pino and Mesa, 2006), but are largely metabolised upon mango wine fermentation (Li et al, 2011(Li et al, , 2012. The hypothesis of the present study was that mango pulp contained more aroma compounds bound as glycosides than the centrifuged mango juice, and that wine yeast would release these bound aroma compounds from the glycosides present in the pulp, which would also compensate for the loss of the terpenes during fermentation.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations